Uso das redes sociais e a experiência do tédio - Rumsey, Sebastian Matheus (Universidade Federal de São Carlos, 2024)
In a contemporary context of acceleration and intensification of the use of social media, this study aims to understand how young adult university students (18 to 25 years old), who report intensive use of the TikTok and/or Instagram social media platforms, narrate their experiences within and outside of these platforms. Additionally, the participants' relationship with boredom and the quality of their experience was investigated. This is a qualitative, exploratory, and cross-sectional study. Five university students participated (aged 20-25 years, including 2 men and 3 women). Each participant was interviewed over four sessions using a semi-structured interview guide. In the last two sessions, in addition to the questions from the guide, 15-minute dynamics of social media use were carried out, interspersed with moments of boredom experience. These dynamics allowed for a clearer and more immediate collection of the investigated phenomena. Data analysis was conducted based on content analysis, with categories derived from the material collected from the interviews and theoretical scope. The following results stand out: the identification and exploration of two different types of social media use, active and passive; the lack of self-reflection by participants regarding their own use; boredom as a short-lived time of stimulus interruption, but central to creating a qualitative change in the narrated experience.
Use of social networks and the experience of boredom
Keywords: Subjetividade; Experiência; Tédio; Sociabilidade digital; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO